Seed Potato Quality Assurance in Ethiopia: System Analysis and Considerations on Quality Declared Assurance Practices - Tessema, L.; Kakuhenzire, R.; McEwan, M. (MDPI, 2025)
Smallholder potato farmers in Ethiopia do not realize the theoretical yield potential of the crop because they do not benefit from the advantages of using quality seed potato of improved varieties. The high disease incidence in seed potatoes has large implications on the potato farming system since the country lacks appropriate seed quality assurance mechanisms. Seed potato quality assurance relies more on the technical support provided by the national research and extension systems than the official seed certification agency. This paper elaborates systematic challenges and opportunities within the potato seed system and poses two research questions: (1) What type of seed quality assurance mechanisms (informal, quality declared, certified) are under implementation in Ethiopia? (2) How does the current seed quality assurance system operate in terms of reliability, accessibility, and quality standards to deliver quality seed potato? The data were collected through face-to-face in-depth key informant interviews with various seed regulatory laboratory managers and technicians in the Oromia, SNNP, and SWEP regions in the main seed- and ware-producing areas of Ethiopia. This was complemented by a comprehensive analysis of relevant documents. The findings show that currently there is no established procedure in place to officially certify early-generation seed potatoes. Two out of six seed quality control laboratories assessed for this study inspected seed potato fields in 2021 but as quality declared seed (QDS), and approved the fields inspected based on visual inspection alone. Our study revealed a weak linkage between early-generation seed (EGS) potato producers, commercial, and QDS seed potato producers, and seed quality control laboratories. Seed potato quality assurance operations were carried out by only a few seed regulatory laboratories with several concerns raised over the effectiveness of quality standards since seed-borne diseases, such as bacterial wilt, have been found at high frequency in the country’s seed potato system. Hence, the current procedures and challenges call for the necessity of upgrading current quality assurance in seed potato certification. Our study underlines the need for policymakers, development partners, and researchers to collaborate and pool efforts to consider transforming the quality declared system to appropriate seed certification. We recommended that institutionalizing novel plant disease diagnostics into seed regulatory frameworks is needed for sustainable potato production and food security in Ethiopia.